The colonial forum of Tarraco. A reappraisal (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
The colonial forum of Tarraco shows characteristics of originality similar to the architectural complex of the forum of Tergeste. It also reveals similarities with other Cisalpine solutions in its urban relationship with the theatre.
Keywords: forum chalcidicum; Tarraco; Tergeste; Eporedia